2021
DOI: 10.1111/and.14014
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo investigation of the therapeutic mechanism of Lycium Chinense and Cuscutae Semen on oligoasthenozoospermia

Abstract: Through network pharmacology research, we found that CYP19, CYP17, AR and SRD5A2 were potential targets for lycium chinense‐cuscutae semen (LC‐CS) treatment of oligoasthenozoospermia. Using in vitro and in vivo experiments, tripterygium glycosides were used to induce spermatogenic dysfunction models in GC‐1spg cells and SD male rats, respectively, and LC‐CS was used to intervene in a spermatogenic dysfunction model. In vitro, LC‐CS could repair the ultrastructure of GC‐1spg cells damaged by tripterygium glycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…After successful model induction, the rats were weighed and anesthetized with pentobarbital sodium (50 mg/kg, intraperitoneally). 18 The rats were then sacrificed by taking blood from the abdominal aorta. Blood from the abdominal aorta was used to detect the level of serum dopamine, and then the penile tissue was isolated for western blotting, quantitative reverse transcription-polymerase chain reaction (qRT-PCR), and hematoxylin and eosin (HE) staining analyses to observe the changes in tissue morphology.…”
Section: Methodsmentioning
confidence: 99%
“…After successful model induction, the rats were weighed and anesthetized with pentobarbital sodium (50 mg/kg, intraperitoneally). 18 The rats were then sacrificed by taking blood from the abdominal aorta. Blood from the abdominal aorta was used to detect the level of serum dopamine, and then the penile tissue was isolated for western blotting, quantitative reverse transcription-polymerase chain reaction (qRT-PCR), and hematoxylin and eosin (HE) staining analyses to observe the changes in tissue morphology.…”
Section: Methodsmentioning
confidence: 99%
“…In our previously reported study, it has been revealed that the core component of Zuogui Wan (Semen Cuscutae‐Lycii Fructus) could enhance the quality of sperms in rats with spermatogenic dysfunction caused by Glucosides of Tripterygium WilforDII Hook. F (Latin name Tripterygii Radix) (GTW) by regulating the testosterone level, but mechanism describing the actions through which Zuogui Wan can regulate testosterone level were not elucidated (Wang, Bao, Meng, Deng, Feng, et al, 2021). Given this fact, the existing study has been designed to evaluate the considerable impact of Zuogui Wan on testosterone regulatory proteins, such as androgen receptor ( AR ), cytochrome p450 family 19 subfamily a member 1 ( CYP19A1 ), cytochrome p450 family 17 subfamily a member 1 ( CYP17A1 ), steroid 5α‐reductaseA2 ( SRD5A2 ) as well as proliferating cell nuclear antigen ( PCNA , Cell proliferation‐related protein) and apoptosis in vitro.…”
Section: Introductionmentioning
confidence: 99%